Theoretical and Historical Trajectory of Sociology in Mexico - Jacqueline Peschard (Revista Mexicana de Ciencias Políticas y Sociales)
Zabludovsky, Gina (2024) Sociology in Mexico. An Intellectual and Institutional History. Springer.